Coconut Water as One of the Optional Oral Electrolyte Solutions - Muzief Munir; I. Mustadjab (Indonesian Pediatric Society, 1980)
In an attempt to overcome mild and moderate dehydration, caused by diarrheal diseases with the outlook of reducing its mortality rate, it seems to be very important to find out many varieties of oral electrolyte solutions which are available in the communities. Our study was performed to evaluate the effectiveness of salt in half strength of coconut water solution as one of the optional oral electrolyte solutions. Children under five years of age with diarrhea were used as subjects in this study, and were divided into two groups, i.e. the ooconut water group and the oratrolyte group (Kimia Parma). The willingness to drink (acceptability)Ã‚Â·, the frequency of diarrhea and vomiting, the severity of dehydration before and after rehydration, and the symptoms and signs of side-effects such as abdominal cramps and hyperkalemia were recorded. From this study it is clear that finely ground salt in half strength of coconut water can be used as an optional oral electrolyte solution with satisfactory results and without any harmful effects.